Organomineral Fertilizers Based Phosphorite Flour Of Central Kyzylkum (Journal of Pharmaceutical Negative Results, 2023)
The article presents the results of studying the effect of a solution of a consortium of microorganisms containing on changes in the chemical composition of composts prepared on the basis of cattle manure and fhosphorite flour of Central Kyzylkum depending on the mass ratio of the initial components and the duration of composting. At the mass ratios of cattle manure: phosphate flour: solution of a consortium of microorganisms = 100: 10: 2 and keeping for 40 days at a reducing the loss of nitrogen and organic matter from 14.68 to 8.91% and from 19.31 to 13.13%, respectively.